Activity-based Protein Profiling Approaches for Transplantation. Issue 9 (September 2019) - Navarrete, Mario; Wilkins, John A.; Lao, Ying; Rush, David N.; Nickerson, Peter W.; Ho, Julie
Abstract : Enzyme activity may be more pathophysiologically relevant than enzyme quantity and is regulated by changes in conformational status that are undetectable by traditional proteomic approaches. Further, enzyme activity may provide insights into rapid physiological responses to inflammation/injury that are not dependent on de novo protein transcription. Activity-based protein profiling (ABPP) is a chemical proteomic approach designed to characterize and identify active enzymes within complex biological samples. Activity probes have been developed to interrogate multiple enzyme families with broad applicability, including but not limited to serine hydrolases, cysteine proteases, matrix metalloproteases, nitrilases, caspases, and histone deacetylases. The goal of this overview is to describe the overall rationale, approach, methods, challenges, and potential applications of ABPP to transplantation research. To do so, we present a case example of urine serine hydrolase ABPP in kidney transplant rejection to illustrate the utility and workflow of this analytical approach. Ultimately, developing novel transplant therapeutics is critically dependent on understanding the pathophysiological processes that result in loss of transplant function. ABPP offers a new dimension for characterizing dynamic changes in clinical samples. The capacity to identify and measure relevant enzyme activities provides fresh opportunities for understanding these processes and may help identify markers of disease activity for the development of novel diagnostics and real-time monitoring of patients. Finally, these insights into enzyme activity may also help to identify new transplant therapeutics, such as enzyme-specific inhibitors.